The Transmission Mechanism of Monetary Policy Shocks in Nigeria: The Interest and Exchange Rates Channels. - Udeaja, Elias A.; Audu, Nathan P.; Obiezue, Titus O. (Advances in Social Sciences Research Journal, 2020)
This paper examines the effectiveness of the interest and exchange rates channels of monetary policy transmission mechanism. The paper employed several statistical cum econometric methodology in a baseline structural vector autoregressive (SVAR) model to evaluate the influence of policy shocks on selected endogenous variables; gross domestic product (GDP), consumer price index (CPI), money supply (MS), treasury bill rate (TBR) and nominal exchange rate (NER) for Nigerian spanning 1981Q1 to 2020Q1. The contemporaneous coefficients in the structural model reveals that key monetary aggregates reacts positively to unexpected changes in the monetary policy instruments. Furthermore, the variance decomposition results indicate that shocks of the selected variables were found to be important for interest rate growth in the short and longer horizons. The exchange rate channel however appears to have a stronger impact on prices. These results mean that depreciation of the nominal exchange rate could be an external deflationary element, particularly for Nigeria.